Enhanced high-energy proton radiation hardness of ZnO thin-film transistors with a passivation layer - Yongsu Lee; Hae-Won Lee; Su Jin Kim; Jeong Min Park; Byoung Hun Lee; Chang Goo Kang (Nano Convergence)
Abstract Metal-oxide thin-film semiconductors have been highlighted as next-generation space semiconductors owing to their excellent radiation hardness based on their dimensional advantages of very low thickness and insensitivity to crystal structure. However, thin-film transistors (TFTs) do not exhibit intrinsic radiation hardness owing to the chemical reactions at the interface exposed to ambient air. In this study, significantly enhanced radiation hardness of Al2O3-passivated ZnO TFTs against high-energy protons with energies of up to 100 MeV is obtained owing to the passivation layer blocking interactions with external reactants, thereby maintaining the chemical stability of the thin-film semiconductor. These results highlight the potential of passivated metal-oxide thin films for developing reliable radiation-hardened semiconductor devices that can be used in harsh space environments. In addition, the relationship between low-frequency noise and defects due to oxygen vacancies was revealed, which can be utilized to improve device reliability.